HUBUNGAN AKTIFITAS FISIK DENGAN KEJADIAN OBESITAS PADA WANITA DI KOTA MALANG - Rahmat, Indra Chasugih; Raharjo, Slamet; Kinanti, Rias Gesang (Jurnal Sport Science, 2017)
Abstract :This research purpose is knowing the correlation between physical activity with woman obesity value in Malang.This research use quantitative approach with correlation research type. This research populationÂ is44 woman do sport in Rampal Field in Malang. Result data is analyzed bypearson product moment correlation.Correlation result between physicalactivity with Woman Obesity Value in Malang is -0,397 or complete negative correlation is 0,397. Then rhitung 0,390>rtabel0,297 with significance part is 5%. So, hypothesisÂ H0 is rejected and H1 is accepted. So correlation model to know the Correlation result between physicalactivity with Woman Obesity Value in Malang is significance. The acceptance of hypothesis H1 can be defined that there is a significance correlation between physicalactivity with Woman Obesity Value in Malang.Keyword :Obesity, Physical Activity